BETWEEN THE PAST AND THE FUTURE: IS REVEALING THE PAST HUMAN RIGHTS VIOLATIONS NECESSARY FOR INDONESIA'S FUTURE? - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
Abstract Problems concerning how to resolve past human rights abuses often come up in the transitional periods. This is because in the previous government such violations were not fully resolved and remained unclear. In the current government, as people demand for justice grows, the government should pay attention for such demand and find a way to resolve the problems. However it is not easy for the government to resolve the problems_ Many obstacles may be faced by the current government to resolve the problems. Insufficient 'ordinary' legal instruments to deal with the past human rights violations and the lack capacity of the legal institutions to deal with the past human rights violations are examples of such obstacles. As the 'ordinary' legal instruments are not sufficient to deal with past human rights violations. there should be another way to resolve the problems. This paper offers a commission to reÂ¬solve the past human rights violation. Unlike the ordinary' legal instruments, this commission aims not only to resolve the past human rights violations but also to find the pattern of such violation so that in the future such violations will not occur. In the end the commission will reconcile the society. Keywords: human rights violations, resolve, commission